2017
DOI: 10.7150/ijbs.19194
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Inhibits Angiogenesis by Inhibiting the Mir-21-5p/TIMP3 Signaling Pathway

Abstract: Angiogenesis provides nutrients and oxygen to promote tumor growth and affords a channel that facilitates tumor cell entry into the circulation. Andrographolide (Andro) possess anti-tumor activity; however, its direct effect on angiogenesis still needs to be clarified. In this study, our experiments revealed that Andro significantly inhibited vascular growth in chick embryo chorioallantoic membrane (CAM) and yolk sac membrane (YSM) models. Meanwhile, tumor angiogenesis was also suppressed by Andro. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…miR-21-5p is considered to be an important tumour-related miRNA. It was found that miR-21-5p was associated with the growth and metastasis of multiple solid tumours 18. In a study investigating brain glioblastoma, miR-21-5p has been highly expressed 19.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21-5p is considered to be an important tumour-related miRNA. It was found that miR-21-5p was associated with the growth and metastasis of multiple solid tumours 18. In a study investigating brain glioblastoma, miR-21-5p has been highly expressed 19.…”
Section: Discussionmentioning
confidence: 99%
“…TIMP3 is directly targeted by miR-21-5p. Andrographolide repressed miR-21-5p and stimulated the expression of TIMP3 [64]. Therefore, it seems clear that andrographolide interferes with angiogenesis mainly through the inhibition of miR-21-5p and upregulation of TIMP3.…”
Section: Regulation Of Micrornasmentioning
confidence: 95%
“…The inhibition of oncogenic miRNAs has been studied contextually in different cancers. MDA-MB-231 cells were cultured on chick embryo chorioallantoic membrane to unveil how andrographolide exerted anti-angiogenic effects [64]. Andrographolide attenuated neovascularization in the tumor tissues in a dose-dependent manner.…”
Section: Regulation Of Micrornasmentioning
confidence: 99%
“…3D, P < 0.05 respectively). We also monitored the anti-angiogenic signaling property of AGP since AGP has been reported to limit angiogenesis signaling in some models [30,31]. Levels of VEGF 165 and FOXM1 in mice harvested 4 h PO AGP treatment showed decreased expression (Fig.…”
Section: Agp Induces Er Stress Tumor Suppressor Gene Expression Andmentioning
confidence: 99%